Task-Based Teaching Practice Perceived by Civil Engineering Students: A Local EFL Context - Doris Sukma; Lena Sastri; Agnes Arum Budiana (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2023)
Task-Based Language Teaching (TBLT) is one of the approaches that can significantly enhance students’ communicative language competence. Numerous studies on TBLT demonstrate favorable outcomes, and a notable number of educators affirm that TBLT is among the effective approaches they can employ. By the same token, many students view TBLT positively. However, a significant portion of recent research seems to concentrate exclusively on English students, while TBLT holds potential applicability for non-English students across various disciplines. These students exhibit distinct characteristics due to language exposure in the classroom. This study investigates non-English students' perception of TBLT practice, specifically civil engineering students at Politeknik Negeri Bengkalis. The purposive sampling technique was used, 47 students who learned English with the TBLT approach. This study utilized a perception questionnaire comprising 17 items. It covers three essential considerations in TBLT namely the nature of tasks (5 items), the difficulty level of tasks (6 items), and the teacher’s roles during the practice (6 items). The finding revealed that non-English students had a positive attitude towards TBLT, as they expressed strong agreement with the positive statements in all three constructs. This shows that TBLT is viewed favorably by English and non-English students alike, regardless of their characteristic differences.